PERFORMANCE, CARCASS YIELD AND LITTER QUALITY OF BROILERS RAISED ON LITTERS TREATED WITH MICRO-ORGANISMS - Dayane Prado da Cruz; Ranulfo Piau Júnior; Luciana Kazue Otutumi; Rodrigo Panucci Cervantes; Taniara Suelen Mezalira; Edson Gerônimo (Ciência Animal Brasileira, 2013)
The present paper aimed at evaluating the effect of adding beneficial micro-organisms to the litters on litter quality, performance and carcass yield for broilers. A total of 240 one-day chicks were used, and randomly distributed in blocks with four treatments and four replications. The following treatments were carried out in the housing: Treatment 1 – Control with weekly spraying of water on the litters; Treatment 2 – Litter treated with a mixture of inoculated and fermented meal by micro-organisms and weekly spraying of water; Treatment 3 – Litter treated by weekly spraying of micro-organisms; Treatment 4 – Litter treated with the same mixture of meals from treatment two and weekly spraying of micro-organisms. Performance was evaluated by the feed consumption, weight gain, feed conversion, viability and carcass, breast and leg yield. From litter samples, pH, dry matter, ashes and nitrogen were evaluated. No differences were found among the treatments. In the conditions the animals were raised, it can be concluded that the treatment on the litter does not affect performance, carcass yield and quality of the litter for broilers. KEYWORDS: feed conversion; Gallus gallus; litter pH; probiotic.